Evaluation of the Impact of 3D Space Building Learning Using Augmented Reality Based on Android Applications - Simanullang, Robintang; Kusuma, Syenina Putri; Tullah, Rahmat; Nurmaesah, Nunung (Institut Teknologi dan Bisnis Bina Sarana Global, 2024)
Mathematics is a subject that is considered difficult by many students, especially geometric materials. Grade 5 students at SDN Bugel 2 had a low average score in learning geometric shapes with an achievement of 40,7. The aim of this research is to increase students' understanding of spatial construction materials in class 5 through learning applications. This research was conducted using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) method. The result of this research is to create a 3D space building learning application based on Augmented Reality which can make it easier for students to understand space building learning. This learning application is effective and can improve student understanding. This is proven by the average quiz score increasing to 81,9.